The comparative characteristic of disposable rotary nickel-titanium files on the basis of cyclic fatigue and the microscopic analysis (Эндодонтия Today)
The problem of a technique of surgical processing of system of root channels remains actual in therapeutic dentistry. Emergence single nickel - titanium rotating tools in dentistry allows to reduce probability of their separation in the root channel. In work results of a pilot study of cyclic fatigue the endodontic machine nickel-titanium tools and their microscopic analysis are considered.